2013
DOI: 10.1128/aem.01804-13
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Imbalances in Sulfur Assimilation and Synthesis of Sulfur-Containing Amino Acids at the Single-Cell Level

Abstract: We describe genetically encoded sensors which transmit elevated cytosolic concentrations of O-acetyl serine (OAS) and O-acetyl homoserine (OAH)-intermediates of L-cysteine and L-methionine synthesis-into an optical output. The sensor pSenOAS3 elicits 7.5-fold-increased fluorescence in cultures of a Corynebacterium glutamicum strain that excrete L-cysteine. Determination of the cytosolic OAS concentration revealed an increase to 0.13 mM, whereas the concentration in the reference strain was below the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Previous studies have reported secretome analyses of C. glutamicum ATCC 13032 and C. glutamicum R, but those studies were performed with the samples of flask cultivations (Hansmeier et al, 2006;Suzuki et al, 2009). Expression of the cg1514 gene has been shown to be up-regulated by CysR which is activated by O-acetyl-L-serine (OAS) or O-acetyl-L-homoserine (OAH) under sulfur limiting condition (Hoffmann et al, 2013;R€ uckert et al, 2008). A similar number of protein spots (approximately 90 spots) were found, with most of the proteins having an acidic pI in the 3.5-4.5 range, however a few proteins had acidic pIs in the 7-8 range (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported secretome analyses of C. glutamicum ATCC 13032 and C. glutamicum R, but those studies were performed with the samples of flask cultivations (Hansmeier et al, 2006;Suzuki et al, 2009). Expression of the cg1514 gene has been shown to be up-regulated by CysR which is activated by O-acetyl-L-serine (OAS) or O-acetyl-L-homoserine (OAH) under sulfur limiting condition (Hoffmann et al, 2013;R€ uckert et al, 2008). A similar number of protein spots (approximately 90 spots) were found, with most of the proteins having an acidic pI in the 3.5-4.5 range, however a few proteins had acidic pIs in the 7-8 range (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that Cg1514 is related to sulfur metabolism in C. glutamicum however the exact function of the protein is still unknown (R€ uckert et al, 2008). Expression of the cg1514 gene has been shown to be up-regulated by CysR which is activated by O-acetyl-L-serine (OAS) or O-acetyl-L-homoserine (OAH) under sulfur limiting condition (Hoffmann et al, 2013;R€ uckert et al, 2008). In our work, however, there was no expectation for elevated cytosolic OAS or OAH concentrations during fed-batch cultivations because the medium used for cultivation, contained 10 g/L of ammonium sulfate and this concentration was high enough not to be limited during the cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…To sense and regulate intracellular or extracellular chemicals, bacteria evolve a variety of transcription factors. Based on this principle, various biosensors for amino acids and their precursors, including l-methionine, l-leucine, l-isoleucine, l-valine [13,14], l-lysine, l-arginine, l-serine, O-acetyl-l-serine [15], O-acetyl homoserine [16], and oxygen [17] have been constructed, and some of these sensors have been successfully applied to the high-throughput screening [12,18,19] and systems metabolic engineering [20]. l-Threonine production in E. coli can be enhanced by regulating IclR [8,9], a transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, biosensor-based strategies were shown to enable the identification of novel and non-intuitive targets for engineering and improving of production strains. Furthermore, the efficient screening of feedback-resistant enzymes (Schendzielorz et al 2014), dynamic pathway regulation (Dahl et al 2013;Liu et al 2015b;Xu et al 2014;Zhang et al 2012), and the analysis of population heterogeneity at the single-cell level (Hoffmann et al 2013;Mustafi et al 2014) demonstrate the broad applicability of biosensors (Liu et al 2015a;Mahr and Frunzke 2016).…”
Section: Introductionmentioning
confidence: 99%